2006
DOI: 10.1002/jrs.1572
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Fe(III)–nitrilotriacetate solutions: study by Raman spectroscopy and ab initio calculations

Abstract: Fe(III)-nitrilotriacetate(NTA) aqueous solutions are used in various redox desulfurization processes. The nature of stable Fe-NTA complexes depends highly on parameters such as [Fe(III)] concentration, NTA/Fe ratio and pH value. These complexes can be characterized by potentiometric measurements or UV-vis spectroscopy, but only at rather low concentrations. Using synthesis of solids, Raman spectra of these solids and ab initio calculations, a rational determination of the nature of complexes stable in water at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Figure shows the vibrational density of states, resembling the Fe–O H 2 O stretching motions of [Fe(MSIDA)(H 2 O) 3 ] + and [Fe(MSNTA)(H 2 O) 2 ] derived via VACFs. The bands in the 450 cm –1 region may result from the Fe–O H 2 O stretching frequencies, which is in agreement with a Raman spectroscopic study of concentrated Fe–NTA solutions, where a band at 410–416 cm –1 was observed which was assigned to a coupling of FeO stretching vibrations and ligand deformations . The Fe–O H 2 O stretching motions of the studied complexes are slightly lower as for Fe(III) in pure water (513 cm –1 ), indicating reduced bond strengths and higher exchange rates.…”
Section: Resultssupporting
confidence: 88%
“…Figure shows the vibrational density of states, resembling the Fe–O H 2 O stretching motions of [Fe(MSIDA)(H 2 O) 3 ] + and [Fe(MSNTA)(H 2 O) 2 ] derived via VACFs. The bands in the 450 cm –1 region may result from the Fe–O H 2 O stretching frequencies, which is in agreement with a Raman spectroscopic study of concentrated Fe–NTA solutions, where a band at 410–416 cm –1 was observed which was assigned to a coupling of FeO stretching vibrations and ligand deformations . The Fe–O H 2 O stretching motions of the studied complexes are slightly lower as for Fe(III) in pure water (513 cm –1 ), indicating reduced bond strengths and higher exchange rates.…”
Section: Resultssupporting
confidence: 88%
“…6,7-Dichloroquinoline-5,8-dione (1) prepared according to Shaikh et al, [16] (10 mg, 0.044 mmol) and dissolved in CH 3 …”
Section: Synthesis and Analysis Of The Complexes For Raman Analysismentioning
confidence: 99%
“…[1] In particular, the investigation of bidentate coordination involving N,O donor atoms, which is of our interest as reported below, has beeen carried out for Fe complexes of benzimidazolyl phenols [2] and nitrilotriacetate. [3] In our recent studies on the synthesis of molecules with potential anti-tumour activity, [4] we investigated the reaction with pyridine and methylacetoacetate of metal complexes where 6,7-dichloroquinoline-5,8-dione is implied as ligand by its N,O donor atoms. Two different products were obtained with the same molecular composition but showing a unit introduced in different regions of the molecule (regioisomers) by a substitution reaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include: Raman spectra of Fe(III)-nitrilotriacetate aqueous solutions were analyzed at high concentrations close to those used in industrial processes by Loridant et al 156 ; a Raman study of the lithium coordination in 1-ethyl-3-methylimidazoliumbis(trifluoromethylsulfonyl)imide (EMI-TFSI) additive systems as lithium-ion battery ionic liquid electrolytes by Hardwick et al 157 ; a solvation structure study of magnesium, zinc, and alkaline earth metal ions in N, Ndimethylformamide, N, N-dimethylacetamide, and their mixtures studied by Raman spectroscopy and DFT calculations; ionic size and electronic effects on steric congestion by Asada et al 158 ; a line shape analyses on the C O stretching bands of acetone using a vibrational coupling model by Kobayashi and Kanesaka 159 ; a Raman and ab initio study of the conformational isomerism in the 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid by Lassègues et al 160 ; a study of the anomalous concentration dependence of the coordination behavior of Cl ion to Ln 3C ion (Ln 3C D rare-earth ion) in anhydrous LnCl 3 alcohol solutions by Yoshimura et al 161 ; experimental and computational studies of the solvation of lithium tetrafluorobrate in dimethyl sulfoxide by Xuan et al 162 ; modeling the physico-chemistry of acid sulfate waters through Raman spectroscopy of the system FeSO 4 -H 2 SO 4 -H 2 O by Sobron et al 163 ; and finally, a Raman spectroscopic study on the dissociation of C 6 F 5 SO 3 Li in two organic solvents with different dielectric constants by Hirankumar et al 164 …”
Section: Other Studies In Liquidsmentioning
confidence: 99%